Atlanto-axial facet displacement during rotational high-velocity low-amplitude thrust: An in vitro 3D kinematic analysis. Issue 6 (December 2015) - Buzzatti, Luca; Provyn, Steven; Van Roy, Peter; Cattrysse, Erik
Abstract: Background: Very little is known about the kinematics of the upper cervical spine in particular during Manual Therapy techniques. In fact no data about displacement of the atlanto-axial joint during High-Velocity Low-Amplitude (HVLA) thrust are available. Knowing the precise kinematics of these vertebrae might allow a better comprehension of such important technique and possible vital structures involvement. Methods: A Zebris CMS20 ultrasound-based motion tracking system was adopted. Twenty fresh human cervical specimens were used in this study. Facet joint displacements of C1 relative to C2 were analysed during three consecutive HVLA thrusts into rotation. Displacement during the thrust and the maximum displacement reached with the manoeuvre were analysed. Results: Descriptive statistics showed a mean Norm displacement during the thrust of 0.5 mm (SD ± 0.5). The maximum displacement, representing the overall facet movement from neutral to end-range position, indicated a Norm value of 6.0 mm (SD ± 3.4). Heterogeneous displacement directions were found during the thrust. Intra and inter-rater reliability reached an insufficient reproducibility level. Considering the amount of displacement induced, no statistical significant differences between the registrations were shown. Conclusion: Displacement during the execution of HVLA thrust is unintentional, unpredictable and not reproducible. On the other hand and in accordance with other studies, the displacement induced with the present technique seems not to be able to endanger vital structure on the Spinal Cord and the Vertebral Artery. This study also adds to a better comprehension of the kinematic of the atlanto-axial segment during the performance of HVLA manipulation. Highlights: We analysed the displacement of in vitro C1–C2 joint facets during HVLA thrust. The displacement induced was unintentional, unpredictable and not reproducible. The displacement induced did not exceed 1 mm during the thrust. The technique seems not to be able to endanger vital structures.